Student Learning Outcome through STEAM Ecobrick Project - Ika Priantari; Aulya Nanda Prafitasari; Novy Eurika; Ali Usman; Kukuh Munandar (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
The world of education is expected to produce students according to the Graduate Competency Standards. To achieve this, it is necessary to apply STEAM-based learning with the Project Based Learning model so that it can improve student learning outcomes related to material environmental pollution in KD 3.8. The main problem is related to non-biodegradable plastic waste, a solution is needed, namely the Ecobrick method in managing plastic waste. This study aims to determine students' cognitive learning outcomes by applying the STEAM Ecobrick Project to cognitive learning outcomes at SMP Muhammadiyah 1 Jember and SMP Muhammadiyah 6 Wuluhan. The method used in this research is quantitative with a comparative type. The sources of data or respondents in the study were seventh grade students of SMP Muhammadiyah 1 Jember and SMP Muhammadiyah 6 Jember. The data collection techniques used are observation, documentation, and questionnaires. The research data were analyzed using SPSS with decision making criteria based on the significance value indicated by the Mann Whitney test output. The results of the Mann Whitney test value of 0.77, meaning that there is no difference in cognitive learning outcomes by applying STEAM Ecobrick Project-based learning to students at SMP Muhammadiyah 1 Jember with students at SMP Muhammadiyah 6 Wuluhan. The average value of cognitive learning outcomes for students of SMP Muhammadiyah 1 Jember is 82.88 and students of SMP Muhammadiyah 6 Wuluhan are 79.81, the difference between the two is 3.07. By implementing STEAM Ecobrick Project-based learning it can improve students' cognitive learning outcomes.